STRATEGI DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA KABUPATEN SIDOARJO DALAM MENGEMBANGKAN WISATA BUDAYA CANDI PARI DI MASA PANDEMI COVID - 19 - Pristiwati Nisya Anggraeni; Meirinawati Meirinawati (Publika, 2022)
Candi Pari is a cultural attraction of majapahit kingdom relics located on Jalan Purbakala, Candi Pari Village, Porong Subdistrict, Sidoarjo Regency. The impact of the Covid-19 pandemic made this tour experience closures resulting in a decrease in the number of visitors. The purpose of this research is to describe the strategy of the Sidoarjo Regency Sports and Tourism Youth Office in developing Pari Temple cultural tourism in order to attract tourists to visit. This research uses descriptive research methods with a qualitative approach. The theory used is the theory of tourism development by Suwantoro which consists of tourist objects and attractions, tourist infrastructure, tourist facilities, infrastructure, and society. The subjects in the study are the Tourism Industry Development Section at the Sports and Tourism Youth Office of Sidoarjo Regency, The Custodian of Pari Temple Cultural Tourism, Society, and Tourists. Data collection techniques use interview, observation, and documentation techniques. Data analysis techniques consist of data reduction, data presentation, data verification, and conclusion withdrawal. The results showed that the development strategy by the Youth Sports and Tourism Office of Sidoarjo Regency went well. This is evidenced by the attraction of tourist attractions in the form of unique buildings and history that managed to attract visitors. Infrastructure related to road access makes it easier for tourists to get to tourist sites. The condition and availability of tourist facilities are quite complete such as toilets, culinary places, and sovenir kiosks. A tourist infrastructure that facilitates travel activities. Positive community response. It can be concluded that the strategy of cultural tourism development of Candi Pari works well despite the shortcomings. These shortcomings include a lack of parking capacity, a lack of promotional strategies by utilizing social media, and public awareness related to tourist conscious villages.